Efficacy and safety of stromal vascular fraction on scar revision surgery: a prospective study - Hyeokjae Kwon; Seokui Lee; Jiyoung Kim; Seung Han Song (Taylor & Francis Group, 2023)
Background Cell-based therapies are popular in the field of reconstructive surgery. The stromal vascular fraction (SVF), comprised of mature adipocytes or blood, reportedly has a regenerative effect; however the mechanism remains unclear. This study aimed to prove the viability and effectiveness of using SVF in scar treatment. Methods This prospective double-blind study involved 20 patients who visited an outpatient clinic for 2 years, from July 2016 to July 2018, and underwent scar revision for traumatic or surgical scars. After scar revision surgery performed by a single surgeon, patient scars were divided into experimental and control sides. The subcutaneous layer of the experimental and control sides were injected with 0.1 mL/cm of SVF and normal saline, respectively. Each side was evaluated using the Patient and Observer Scar Assessment Scale (POSAS) before and six months after the surgery. Results Of the 20 patients who underwent scar revision surgery and SVF treatment, 4 dropped out for personal reasons. In 11 of 12 POSAS items, the experimental side showed significant improvements compared to the control side. Conclusions Although more research is needed, autologous SVF is a valuable source of regenerative medicine that can be swiftly and inexpensively prepared from human fat tissue.